Akad E-Commerce Jual Beli Online Ditinjau dari Kompilasi Hukum Ekonomi Syariah - Putri, Juliana Dwi; M. Randhika Priyatna; M. Naufal Empy; Fathoni Yusuf; Fadhli Suko Wiryanto4 (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2023)
The problem discussed in this article is how the review of the types of online buying and selling transactions in e-commerce in Indonesia is reviewed from the compilation of sharia economic law. The expected beneﬁts of this research include eliminating doubts in choosing the type of online buying and selling transactions in e-commerce in Indonesia and knowing the types of online buying and selling transactions (peer to peer) in e-commerce in Indonesia that are in accordance with Islamic law. This research uses a qualitative research approach, where this scientiﬁc method is used to build knowledge through understanding and discovery. The results of this study indicate that in conducting E-commerce transactions, there are two sales and purchase contracts that can be used, namely the salam and Istisna contracts. If the salam contract, the buyer makes a payment in advance and the product speciﬁcations are clearly stated and the delivery of the goods is delayed, while the Istishna contract, the speciﬁcations of the goods have been agreed upon by the buyer and seller then an order is made in advance or the goods have not / are being made.